2016
DOI: 10.1007/s11340-016-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermographical Analysis of Paper During Tensile Testing and Comparison to Digital Image Correlation

Abstract: The thermal response in paper has been studied by thermography. It was observed that an inhomogeneous deformation pattern arose in the paper samples during tensile testing. In the plastic regime a pattern of warmer streaks could be observed in the samples. On the same samples digital image correlation (DIC) was used to study local strain fields. It was concluded that the heat patterns observed by thermography coincided with the deformation patterns observed by DIC. Because of its fibrous network structure, pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
(22 reference statements)
1
14
1
Order By: Relevance
“…6b, that the temperature decreased first in the elastic region of the stress-strain curve and then increased considerably after reaching the plastic region. This behavior is well in line with previous studies and can be explained with thermoelastic effect (Dumbleton et al 1973;Hagman and Nygårds 2017). The increase of the temperature at 0.7% strain (red line) indicates the onset of fiber-fiber bond failure, which, as discussed above, is caused by the heat dissipation of the strain energy in the fibers when the bonds break.…”
Section: Global Mean Properties Of the Investigated Kraft Papersupporting
confidence: 91%
See 3 more Smart Citations
“…6b, that the temperature decreased first in the elastic region of the stress-strain curve and then increased considerably after reaching the plastic region. This behavior is well in line with previous studies and can be explained with thermoelastic effect (Dumbleton et al 1973;Hagman and Nygårds 2017). The increase of the temperature at 0.7% strain (red line) indicates the onset of fiber-fiber bond failure, which, as discussed above, is caused by the heat dissipation of the strain energy in the fibers when the bonds break.…”
Section: Global Mean Properties Of the Investigated Kraft Papersupporting
confidence: 91%
“…The local deformation was investigated microscopically and the local basis weight by gravimetrically measuring the local regions of fibrous networks. Korteoja et al (1998) as well as Hagman and Nygårds (2017) concluded that locally high tensile strain and tensile damage occurred in the regions with low basis weight. Besides, Wong et al (1996) found that the rupture of paper initiated from the region with low basis weight and high strain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The causes of dampness may be [4]:  Precipitation;  capillarity of groundwater;  condensation of steam or sanitary installation breakdowns;  technological processes connected with erecting buildings.…”
Section: Introductionmentioning
confidence: 99%